Pelayanan Akta Kelahiran Anak di Wilayah Perbatasan Provinsi Nusa Tenggara Timur - Penny Naluria Utami (Jurnal HAM, 2014)
There are only 55% of Indonesian childs who already have birth certificate until the end of December 2009 according to Indonesian Child Protection Commission. Child birth certificate service is running slow, because most of the local governments still make the issuance of birth certificates as a source of local revenue, and there are only 250 districts/ cities that already provide free birth certificate issuance policy for its citizens. Several factors that affect the low birth registration including: the lack of information to the public, the costs are very high in case of late registration, and the low quality of access management in the district/city level. The problem in this paper is to describe on how the government policy in providing service of child birth certificate in the border region of East Nusa Tenggara; and also to describe on how the child birth certificate services in the border region of East Nusa Tenggara. The scope of analysis taken is limited to the policies of central and local governments and their implementation in the issuance of child birth certificate in the border region of East Nusa Tenggara. The method of study used is qualitative approach, while the source of data consists of primary and secondary data. The results shows that every Indonesian citizen has the right to identity in the form of citizen legal document.